A Retrospective Database Analysis of Neonatal Morbidities to Evaluate a Composite Endpoint for Use in Preterm Labor Clinical Trials - Jeanne M. Pimenta; Myla Ebeling; Timothy H. Montague; Kathleen J. Beach; Jill Abell; Michael T. O'Shea; Marcy Powell; Thomas C. Hulsey (American Journal of Perinatology Reports, 2018)
Abstract